PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA KARYAWAN DAN KOMITMEN ORGANISASI PADA PT. KPM - Kadek Sintha Dewi (Faculty of Economics and Business Udayana University, 2013)
The research objective was to determine the transformational leadership style influence on employees job satisfaction and organizational commitment on PT. KPM. The sample in this study was 30 people and data were processed using Partial Least square (PLS). The results showed significant effect of transformationalleadership style on employee job satisfaction, employee satisfaction significant influence on organizational commitment, and transformational leadership style indirect effect on organizational commitment. To foster employee job satisfaction and organizational commitment, the company needs to consider the needs of employees as well as payment